Demographical Study of Individuals with Allergy to Dust Storms in Basra - Nibras S. Al-Ammar; Saad Sh. Hamadi (Al-Qadisiyah Journal of Pure Science, 2017)
This study was carried out in College of Medicine, University of Basra during the period between (June –September) 2011 to know the distribution of individuals in Basra with allergy to dust storms according to gender, age groups, symptoms, and family history of allergy to dust storms. 314 individuals were included in this study,238 individuals have allergy to dust storms and 76 have no allergy to dust storms and considered as controls. There was no significant difference between allergic individuals and controls according to gender and age groups. There was a significant association between allergy to dust storms and presence of symptoms of nasal secretions, eye irritation, breathing difficulties; P-value< 0.05; odds ratio (OR)=16.5 ; 95% Confidence Interval (CI)= (8.02-33.97), P-value< 0.05; odds ratio (OR)=4.22; 95% Confidence Interval (CI)= (2.30-7.74) and P-value=0.00; odds ratio (OR)=16.17; 95% Confidence Interval (CI)= (7.41-35.27) respectively. Also there was a significant association between allergy to dust storms and presence of allergy to perfume, smoke, food and drug; P-value=0.001; odds ratio (OR)= 3.93; 95% Confidence Interval (CI)= (1.63-9.52), P-value=0.01; odds ratio (OR)=2.19; 95% Confidence Interval (CI)= (1.20-3.98), P-value=0.004; odds ratio (OR)=2.43; 95% Confidence Interval (CI)= (1.34-4.42) and P-value=0.005; odds ratio (OR)=3.97; 95% Confidence Interval (CI)= (1.38-11.45) respectively. Results showed no significant association with family history of allergy to dust storms and duration of outdoors period.